2010
DOI: 10.1007/s10126-010-9279-x
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Control of Fish Diseases

Abstract: All metazoans possess innate immune defence system whereas parameters of the adaptive immune system make their first appearance in the gnathostomata, the jawed vertebrates. Fish are therefore the first animal phyla to possess both an innate and adaptive immune system making them very interesting as regards developmental studies of the immune system. The massive increase in aquaculture in recent decades has also put greater emphasis on studies of the fish immune system and defence against diseases commonly asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
303
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 601 publications
(333 citation statements)
references
References 268 publications
4
303
0
4
Order By: Relevance
“…Low or excess levels of lipids decrease immune function, induce oxidative damage and apoptosis and impair the antioxidant system in the skin of young grass carp Fish skin is an important immune organ, which has an essential role in protection against invasive pathogens [111]. Thus, we found a scoring system to evaluate skin haemorrhage and lesions during A. hydrophila infection, similar to that of Song et al [58].…”
Section: 32mentioning
confidence: 77%
“…Low or excess levels of lipids decrease immune function, induce oxidative damage and apoptosis and impair the antioxidant system in the skin of young grass carp Fish skin is an important immune organ, which has an essential role in protection against invasive pathogens [111]. Thus, we found a scoring system to evaluate skin haemorrhage and lesions during A. hydrophila infection, similar to that of Song et al [58].…”
Section: 32mentioning
confidence: 77%
“…Phagocytes are major innate immune molecules which show respiratory or oxidative burst activity by releasing bactericidal reactive oxygen species (ROS) upon stimulated by PAMPs through receptors or by the uptake of pathogens (Magnadottir 2010). However, excessive production of these ROS may lead to oxidative stress in fish.…”
Section: Discussionmentioning
confidence: 99%
“…Its structure and function reflect the adaptation of the organism to the physical, chemical, and biological properties of the aquatic environment and the natural history of the organism. The aquatic environment is rich in pathogenic organisms [26]; hence, the skin of aquatic vertebrates is extremely important as the first line of defence against the invasion of environmental pathogens, and it is just important to the respiratory and digestive organs. Because of the intimate contact of fish with the environment, cutaneous diseases are relatively more common in fish than in terrestrial vertebrates and are one of the primary disease conditions presented to the aquatic animal practitioner [27].…”
Section: Teleost Skinmentioning
confidence: 99%
“…Both the number of goblet cells and the composition of the mucus which they produce may vary depending on their location. On the other hand, fine structural studies have demonstrated that the epidermis of fishes may have two different types of glandular cells, namely, goblet cells and club cells [26,57]. The slipperiness of the mucus is considered to be a result of the presence of high molecular weight gel-forming macromolecules, and it is assumed that the predominant gel-forming macromolecules in mucus are glycoproteins.…”
Section: Teleost Skinmentioning
confidence: 99%